CISH and IHC for the Simultaneous Detection of ZIKV RNA and Antigens in Formalin‐Fixed Paraffin‐Embedded Cell Blocks and Tissues. Issue 12 (22nd December 2021) - Corchuelo, Sheryll; Gómez, Claudia Y.; Rosales, Alicia A.; Santamaria, Gerardo; Rivera, Jorge Alonso; Saad, Edgar Parra; Torres‐Fernández, Orlando; Rengifo, Aura Caterine
Abstract: Zika virus is an arthropod‐borne virus that has recently emerged as a significant public health emergency due to its association with congenital malformations. Serological and molecular tests are typically used to confirm Zika virus infection. These methods, however, have limitations when the interest is in localizing the virus within the tissue and identifying the specific cell types involved in viral dissemination. Chromogenic in situ hybridization (CISH) and immunohistochemistry (IHC) are common histological techniques used for intracellular localization of RNA and protein expression, respectively. The combined use of CISH and IHC is important to obtain information about RNA replication and the location of infected target cells involved in Zika virus neuropathogenesis. There are no reports, however, of detailed procedures for the simultaneous detection of Zika virus RNA and proteins in formalin‐fixed paraffin‐embedded (FFPE) samples. Furthermore, the chromogenic detection methods for Zika virus RNA published thus far use expensive commercial kits, limiting their widespread use. As an alternative, we describe here a detailed and cost‐effective step‐by‐step procedure for the simultaneous detection of Zika virus RNA and proteins in FFPE samples. First, we describe how to synthesize and purify homemade RNA probes conjugated with digoxygenin. Then, we outline the steps to perform the chromogenic detection of Zika virus RNA using these probes, and how to combine this technique with the immunodetection of viral antigens. To illustrate the entire workflow, we use FFPE samples derived from infected Vero cells as well as from human and mouse brain tissues. These methods are highly adaptable and can be used to study Zika virus or even other viruses of public health relevance, providing an optimal and economical alternative for laboratories with limited resources. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of RNA probes conjugated with digoxigenin (DIG) Basic Protocol 2 : Simultaneous detection of ZIKV RNA and proteins in FFPE cell blocks and tissues